2001
DOI: 10.1073/pnas.231320498
|View full text |Cite
|
Sign up to set email alerts
|

Paternity and relatedness in wild chimpanzee communities

Abstract: The genetic structure of three contiguous wild chimpanzee communities in West Africa was examined to determine the extent to which the community, the mixed-sex social unit of chimpanzees, represents a closed reproductive unit. An analysis of paternity for 41 offspring resulted in 34 cases of paternity assignment to an adult male belonging to the same community. Among the 14 offspring for which all potential within-community fathers have been tested, one likely case of extra-group paternity (EGP) has been ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
180
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 249 publications
(191 citation statements)
references
References 37 publications
8
180
3
Order By: Relevance
“…In the three primate populations where paternal sibling nepotism has been studied (rhesus macaques at Cayo Santiago, baboons at Amboseli, and chimpanzees at Ngogo), the majority of similarly aged dyads do not consist of paternal siblings (Table 1, second row). Age proximity may not be a reliable cue for paternal sibship in these populations because male reproductive skew at any given time is not extreme, and males produce offspring throughout their entire adult life rather than only during a narrow time window (32)(33)(34)(35)(36). At Ngogo, patterns of male reproduction result in a situation where members of different age cohorts are as closely related to each other as individuals of the same age cohort (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the three primate populations where paternal sibling nepotism has been studied (rhesus macaques at Cayo Santiago, baboons at Amboseli, and chimpanzees at Ngogo), the majority of similarly aged dyads do not consist of paternal siblings (Table 1, second row). Age proximity may not be a reliable cue for paternal sibship in these populations because male reproductive skew at any given time is not extreme, and males produce offspring throughout their entire adult life rather than only during a narrow time window (32)(33)(34)(35)(36). At Ngogo, patterns of male reproduction result in a situation where members of different age cohorts are as closely related to each other as individuals of the same age cohort (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As we will see below, coalitions can serve different functions (van Schaik et al, 2006); they can be observed among different sex and age classes (reviewed in Chapais, 1995); they can involve kin (e.g., Riss & Goodall, 1977;Chagnon & Bugos, 1979;Wahaj et al, 2004), non-kin (e.g., Vigilant et al, 2001;Langergraber et al, 2007;Schülke et al, 2010), and friends or acquaintances (Hruschka & Henrich, 2006;Hruschka, 2010). As this brief review makes clear, coalitionary patterns are varied, and understanding this diversity would be greatly enhanced by formal modelling that would allow us to identify the general conditions under which coalition formation is expected to evolve, characterize the degree of variability expected, and predict when coalitions should, and should not, occur.…”
Section: A Brief Primer On Coalition Formationmentioning
confidence: 99%
“…Observations of female white-faced capuchins, gorillas and white-nosed coatis also reveal that, like female Old World monkeys, individuals are more likely to aid their kin instead of non-kin in disputes (Watts, 1997;. In studies of white-faced capuchins, Barbary macaques, bonnet macaques, chimpanzees and bottlenose dolphins, males sometimes form coalitions with their kin more often than with non-kin (Silk, 1992;Widdig et al, 2000;Langergraber et al, 2007; but see Vigilant et al, 2001). In some species mothers are known to provide aid to sons in conflicts with other males (Surbeck et al, 2011; see also Chapais, 1983;Kutsukake & Hasegawa, 2005).…”
Section: Kinshipmentioning
confidence: 99%
“…Instead, DNA obtained from wadges, faeces, plucked hairs and shed hairs collected from night nests has provided a wealth of data on phylogeography, gene flow, social structure and kinship in wild chimpanzees (Constable et al 2001;Vigilant et al 2001), gorillas (Jensen-Seaman and Kidd 2001), bonobos (Gerloff et al 1999), Hanuman langurs (Launhardt et al 2001), orangutans (Utami et al 2002) and lemurs (Nievergelt et al 2002). Microsatellite genotyping was performed on faecal samples from an Indonesian orangutan (Pongo pygameus abelii) population that has been the subject of a long-term behavioural study with an emphasis on male reproductive strategies (Utami et al 2002).…”
Section: Non-invasive Samples As a Novel Source Of Phylogenetic Popumentioning
confidence: 99%
“…Fernando et al 2000;Garnier et al 2001;Vigilant et al 2001;Utami et al 2002). This number is likely to increase, as more researchers become aware of the vast potential for molecular analysis in gleaning useful biological data from non-invasive samples.…”
Section: Introductionmentioning
confidence: 99%